2023
DOI: 10.1021/acsapm.3c01534
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable 3D-Printed Composite Hydrogel Containing Rice Husk Biochar for Organic Contaminants Adsorption in Tap Water

Emilly C. Silva,
Victória R. Soares,
Andressa B. Nörnberg
et al.

Abstract: Water and wastewater treatment face significant challenges in removing organic contaminants, and the search for efficient processes and materials is crucial to reducing this issue. Herein, the design and manufacturing of 3D-printed composite hydrogels using a combination of alginate and rice husk biochar was proposed. These composite hydrogels were evaluated as adsorbents for removing ibuprofen (IBU) and methylene blue (MB) from tap water. Various characterization techniques, including FTIR, XRD, SEM, and BET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Researchers have recently created recyclable 3D printed hydrogel composites that incorporate biochar sourced from rice husk for removing organic contaminants from tap water and have experimentally demonstrated that the hydrogel containing 10% w/w biochar (Alginate/Biochar) demonstrated significant adsorption capacities of 111.4 mg/g for ibuprofen (IBU) and 214.6 mg/g for methylene blue (MB) which represents an increase in adsorption capacities of 48% (IBU) and 58% (MB) compared to conventional hydrogels without biochar. This innovative development highlights the potential of novel composites and underscores the importance of continuing to explore new avenues for improving water quality ( Silva et al, 2023 ).…”
Section: Applications Of 3d Printing In Bioremediationmentioning
confidence: 95%
“…Researchers have recently created recyclable 3D printed hydrogel composites that incorporate biochar sourced from rice husk for removing organic contaminants from tap water and have experimentally demonstrated that the hydrogel containing 10% w/w biochar (Alginate/Biochar) demonstrated significant adsorption capacities of 111.4 mg/g for ibuprofen (IBU) and 214.6 mg/g for methylene blue (MB) which represents an increase in adsorption capacities of 48% (IBU) and 58% (MB) compared to conventional hydrogels without biochar. This innovative development highlights the potential of novel composites and underscores the importance of continuing to explore new avenues for improving water quality ( Silva et al, 2023 ).…”
Section: Applications Of 3d Printing In Bioremediationmentioning
confidence: 95%
“…Properties. Applying Fourier transform infrared (FTIR) spectroscopy, 32 the chemical composition of the DCS-PNIPAm gel was ascertained, as seen in Figure 2a. The presence of isopropyl groups is shown by the characteristic peak at ≈1131 cm −1 , which is recognized as an isopropyl strand vibrational absorption peak.…”
Section: Characterization Of Composition and Structuralmentioning
confidence: 99%
“…The organic polluting wastewater also causes a serious of problems in environmental pollution and economic loss 5–10 and poses a big threat to the ecological environment 11,12 . Compared with the biodegradation, chemical coagulation, combustion method, and gravity sedimentation, 13–15 membrane separation displaying the merits in convenient operation, environmentally friendly, and high separation efficiency has become an effective strategy in oil–water separation and spilled‐oil recovery in recent years 16–22 . However, the practical wastewater usually contains complex compositions, such as different types of oils, organic pollutants, heavy metal residues, antibiotics, and bacteria.…”
Section: Introductionmentioning
confidence: 99%